High-Volume Fly Ash-Based Cementitious Composites as Sustainable Materials: An Overview of Recent Advances - Sen Du; Qingxin Zhao; Xianming Shi (Advances in Civil Engineering)
High-volume fly ash (HVFA) cementitious composites (paste, grout, mortar, and concrete) have been widely investigated as a class of sustainable materials due to their lower carbon footprint and often better life cycle performance than conventional Portland cement mixtures. Recent years have seen increased research in HVFA-based materials, and the potential of this type of mixtures in engineering applications has significantly improved. In this context, this work reviews the renewed knowledge of HVFA mixtures, focusing on the relevant papers published over the last decade. The effects of replacing cement with a HVFA binder on the fresh properties, mechanical properties, durability performance, and environmental impact of HVFA cementitious composites are explored. Measures that can compensate for the main drawbacks that limit the wider application of HVFA mixtures are discussed in detail. At last, we summarize the research needs and remaining challenges of HVFA cementitious composites.